EDITORIAL - Green, Sulina (Social Work/Maatskaplike Werk, 2004)
This year South Africans celebrated their first ten years of democracy, a decade of remarkable changes which two former presidents, F W de Klerk and Nelson Mandela, critically evaluated in consecutive addresses they made to a joint session of Parliament